Stratigraphy, structure and geology of Late Miocene Verkhneavachinskaya caldera with basaltic-andesitic ignimbrites at Eastern Kamchatka - Bergal-Kuvikas,O.; Leonov,V.; Rogozin,A.; Bindeman,I.; Kliapitskiy,E.; Churikova,T. (Journal of Geosciences, 2019)
We newly describe a paleovolcano in the Eastern Volcanic Belt of Kamchatka named Verkhneavachinskaya caldera (VC). According to geological mapping of the area covered by the deposits, mainly lava-like ignimbrites, the VC is interpreted as an eroded paleoshield volcano with a summit caldera. It is one of the largest (10 × 12 km diameter) and oldest (c. 5.78-5.58 Ma as newly dated by the Ar-Ar method) currently known paleovolcanoes in Kamchatka with such a good preservation. The lava-like welded ignimbrites correspond to basaltic andesite and andesite and are more mafic than pyroclastic rocks from the other post-Pliocene calderas in Kamchatka. The deposits of VC are interbedded layers of welded ignimbrites and volcaniclastic deposits. These deposits were formed during long-lived, continuous eruptions of hot pyroclastic flows and subsequent accumulations of volcaniclastic deposits (e.g. lahars). The VC provides new insights into the early stages of Eastern Volcanic Belt development after the Kronotsky Arc Terrane accretion. This potentially explains the origin of voluminous basaltic-andesitic ignimbrites formed on thin crust during the initial stage of the arc formation.
Keywords: Kamchatka; Verkhneavachinskaya caldera; mafic ignimbrites; welded ignimbrites